The role of selenium on autophagy - Febriana Kurniasari; Hanna Goenawan; Astrid Feinisa Khairani; Sunarjati Sudigdo Adi; Ronny Lesmana; Setiawan (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Selenium (Se) deficiency is associated with certain abnormalities, such as Keshan disease, cancer, cardiovascular disease (CVD), viral infections, infertility, immune system abnormalities, metabolic diseases, neurological disorders, and growth retardation. Its antioxidant properties are integrated into various selenoenzymes, mainly glutathione peroxidase (GPx) and thioredoxin reductase (Trx). These selenoenzymes act as a protective mechanism to prevent oxidative stress-induced cellular injury, regulate DNA transcription, and cell proliferation. Decreased levels of antioxidants induce reactive oxygen species (ROS) accumulation resulting in loss of mitochondrial structure and function. The antioxidant properties of selenium could depress ROS and modulates autophagy by interfering initiation of autophagy and phagophore formation. Inhibition at the initiation stage not only involves mTOR and AMPK, an autophagy-related regulators, but also autophagy markers, including Beclin 1, Atg5, LC3, and p62; thus, phagophore and autophagosome are not formed. This review will discuss the role of selenium in modulating autophagy in various organs.